Pendampingan Profesionalisasi UMKM: Peningkatan Branding dan Perolehan Legalitas Usaha (NIB & P-IRT) pada Kedai Permai - Desi Rahmadani Siagian; Romie Jhonnerie; Fadhiilatun Nisaa; Riska Fatmawati; Putriana Sari Sirait; Nur Asiah (Unri Conference Series: Community Engagement, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often face fundamental challenges in business professionalism, particularly related to suboptimal product branding and the absence of formal legality. These conditions significantly hinder the competitiveness and market access of MSMEs in an increasingly competitive environment. This community service activity aims to assist Kedai Permai MSME in Kampung Kayu Ara Permai in professionalizing its business through two strategic interventions: improving product label design and facilitating the issuance of a Business Identification Number (NIB) as well as a Home Industry Food Production Certificate (P-IRT). The method used is participatory mentoring, involving active collaboration with the business owner from the conceptual design stage, technical facilitation, up to the issuance of legal documents. The outcomes of this activity include the creation of a new label design that is more informative and visually appealing for mangrove dodol and syrup products, as well as the successful acquisition of NIB and P-IRT by Kedai Permai MSME. These achievements represent a strategic step that not only enhances brand identity and consumer trust but also expands market access and establishes a solid foundation for sustainable business growth.